Diffuse multiple scattering. Issue 1 (18th December 2014) - Nisbet, A. G. A.; Beutier, G.; Fabrizi, F.; Moser, B.; Collins, S. P.
<x xml:space="preserve">Abstract</x> A new form of diffraction lines has been identified, similar to Rutherford, Kikuchi and Kossel lines. This paper highlights some of the properties of these lines and shows how they can be used to eliminate the need for sample/source matching in Lonsdale's triple convergent line method in lattice‐parameter determination.